Detección de Microcystis y microcistina mediante la Reacción en Cadena de la Polimerasa - Chávez Luzanía, Roel Alejandro (2024)
Cyanobacteria are photosynthetic organisms important in multiple biosphere life cycles; however, genera such as Microcystis have the ability to form blooms and produce cyanotoxins that compromise water quality This study aimed to validate the use of endpoint PCR to detect cyanobacteria, the genus Microcystis, and their genetic ability to produce microcystins. Three oligonucleotide pairs were used for the 16S rRNA gene of cyanobacteria and Microcystis, as well as mcyA. The use of end-point PCR allowed the specific detection of cyanobacteria and Microcystis in cell concentrations up to 10 times below the bloom alert limit, as well as the detection of the mcyA gene, both in isolated strains and in a simulated microbial community. The effectiveness of using end-point PCR for the specific detection of cyanobacteria makes it an early monitoring tool, capable of predicting potential microcystin production and thus contributing significantly to water quality management.